Providing Health Counseling On The Introduction Of “ISI PIRINGKU” At Nurul Ikhsan Mosque RT 24, Kel. Sawah Lebar, Bengkulu City - Wasi, Chyntia Four; Saputri , Novi Transiska Sari; Angraini , Neti; Suyanto, Jipri (Universitas Dehasen Bengkulu, 2024)
. Isi Piringku is a program for the community to understand how to eat the right portion to meet nutritional needs. The contents of my plate are a replacement for the concept of 4 Healthy 5 Perfect. The old concept no longer accommodates the fulfillment of balanced nutrition. The portion of My Plate consists of staple foods, namely carbohydrate sources with a portion of 2/3 of 1/2 of a plate. Then it comes with side dishes with a portion of 1/3 of 1/2 plate. For the other half of the plate, it is filled with a proportion of vegetables with a portion of 2/3 and fruits with a portion of 1/3 (Ministry of Health 2022). Balanced nutrition with the composition of the contents of my plate is a reference for people in consuming food and drinks in a balanced manner. It can reduce the fatality of covid-19 infection, because patients exposed to covid-19 are prone to malnutrition. There is a synergistic relationship between malnutrition and infections that can increase in the conditions of the Covid-19 pandemic (Permatasari et al., 2020).